Some Remarks on Close-to-Convex and Strongly Convex Functions
We consider questions of the following kind: When does boundedness of |{1+zp’(z)/p(z) |, for a given analytic function p, imply boundedness of |{p(z) |? The paper determines the order of strong close-to-convexity in the class of strongly convex functions. Also, we consider conditions that are sufficient for a function to be a Bazilevič function. , number=2, journal=MATHEMATICA SCANDINAVICA, author=Trąbka-Więcław, Mamoru Nunokawa, Janusz Sokół, Katarzyna, year=2015, month=Jun., pages=309–319